TITLE: INFLUENCE OF SOIL COMPACTION ON ENERGY EFFICIENCY DURING TILLAGE OPERATIONS - Aziza Tajimuratova (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  Soil  compaction  is  a  significant  factor  influencing  the  energy efficiency of tillage operations in agriculture. The present review is concerned with an examination  of  the  extant  literature  on  the  manner  in  which  compaction  increases energy  requirements  during  tillage,  and  the  concomitant  implications  of  this phenomenon in regard to the economic and environmental impact of farming. The article explores the mechanisms through which soil compaction affects energy usage, the  long-term  consequences  of  increased  tillage  depth,  and  potential  mitigation strategies. The review concludes by exploring sustainable farming practices, including reduced tillage, precision farming, and subsoiling, as potential solutions to enhance energy efficiency in the context of soil compaction.